Impact of Savings on Economic Growth in Africa - Gidigbi, Matthew O; Donga, Manu (The Economics and Finance Letters, 2020)
This paper investigates the impact of savings on economic growth in Africa. Annual data covering thirty African countries based on data availability for the period of thirty-five years starting from 1980 were used. The study was found to be imperative because extant studies in this line were of mixed results. Panel Estimated Generalised Least Squares (EGLS) with pooled, fixed and random effects estimations were carried out, but Pooled Panel EGLS with cross-section Seemingly Unrelated Regression (SUR) weight estimation was explained. The study revealed that savings contribute 3.96 per cent to economic outputs when increased by a percentage. Meanwhile, a per cent increment in each of the foreign direct investment (FDI) and current account balance will positively impact economic growth by 18.7 and 4.6 per cent respectively. Also, there is no causality between domestic saving and economic growth. But bidirectional causality exists between foreign direct investment and domestic saving. The study concluded that saving is relevant to economic growth in Africa, though, its contribution is very low when compared to FDI’s impact but very important. The current account balance is very relevant to foreign direct investment and domestic saving. It is recommended that policies favouring savings should be encouraged such as universal coverage pension and grass-roots oriented saving schemes. Also, a surplus current account balance should be maintained in the continent to attract more foreign direct investment and improve domestic savings.